Dabigatran etexilate in a vitamin‐K antagonist non responder patient during Heartware HVAD support. Issue 2 (17th January 2017) - Baronetto, Andrea; Centofanti, Paolo; Attisani, Matteo; Boffini, Massimo; Ricci, Davide; Simonato, Erika; Rinaldi, Mauro
Abstract: We report a case of a patient supported with a HeartWare left ventricular assist device for idiopathic cardiomyopathy who was resistance to vitamin‐K antagonists three months after implantation. The patient initially started low‐molecular‐weight heparin therapy and then, after the onset of an ischemic stroke, switched to dabigatran etexilate (DE). The patient had progressive recovery of cardiac function for which the device was explanted. No thrombotic or bleeding events occurred during DE therapy.